2015
DOI: 10.12659/msm.895381
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ability of Some CANTAB Battery Test Measures to Detect Cognitive Response to a Single Dose of Donepezil in Alzheimer Disease

Abstract: BackgroundThe Cambridge Neuropsychological Test Automated Battery (CANTAB) was used to explore which tests and their measures are able to detect cognitive change after a single dose of donepezil in Alzheimer disease (AD) patients. The aim of this study was to establish the ability of CANTAB tests and their measures to detect cognitive change after a single 5-mg dose of donepezil in treatment-naïve AD patients.Material/MethodsWe enrolled 62 treatment-naïve AD patients and 30 healthy controls in this prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The utilization of PIFCs in medical diagnosis and the biological interpretation of the neural network involved would also benefit from research on Fechner illusory colors in AD [27]. The decline in blue opponent perception, if properly standardized, may be used as a cheap and noninvasive diagnostic marker in early diagnosis of AD as an addition to other cognitive, electrophysiologic, behavioral, and emotional regulation methods [2831]. On the other hand, the pattern of decline in perception of Fechner illusory colors in people with AD can be helpful for further research in order to understand the nature of visual perception of color, and may have even broader implications for the fundamental mind-body relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of PIFCs in medical diagnosis and the biological interpretation of the neural network involved would also benefit from research on Fechner illusory colors in AD [27]. The decline in blue opponent perception, if properly standardized, may be used as a cheap and noninvasive diagnostic marker in early diagnosis of AD as an addition to other cognitive, electrophysiologic, behavioral, and emotional regulation methods [2831]. On the other hand, the pattern of decline in perception of Fechner illusory colors in people with AD can be helpful for further research in order to understand the nature of visual perception of color, and may have even broader implications for the fundamental mind-body relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome variables selected for each CANTAB test was based on their sensitivity to detect changes in ageing and AD (Egerhazi et al, ; Fowler et al, ; Nathan et al, ; Swainson et al, ) and the demonstrated sensitivity of the tests and outcome variables to pharmacological modulation (both acute and chronic treatment) in both healthy young and older subjects (Elliott et al, ; Yurko‐Mauro et al, ) as well as patients with AD (Kuzmickiene & Kaubrys, ).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the most used drugs to treat AD are the inhibitors of the enzyme acetylcholinesterase [61,62], as donepezil [62][63][64][65][66], which acts by increasing the availability of acetylcholine in the synaptic space of cholinergic neurons [62,67,68]. Another drug used is memantine, which is a pharmacological antagonist of glutamatergic receptor N-methyl-D-aspartate (NMDA) [62,69,70].…”
Section: Improving Mitochondrial Health As a Valid Therapy For Admentioning
confidence: 99%